EKSPRESI JAM GADANG GAYA ILUSI OPTIK PADA KRIYA LOGAM - Alfian Nur; Sumadi Sumadi; Hendra Hendra (Institut Seni Indonesia Padangpanjang, 2021)
Jam Gadang is a historic clock tower building located in the city of Bukittinggi. Jam Gadang has several unique and historical journey that is characteristic. This paper contains the concept of metal craft creation with optical illusion art. The method of creating works of art exploration, design, and creation of artwork. Artworks were created as interior decoration. The result of the concept contains three artworks;